1972
DOI: 10.1113/jphysiol.1972.sp009886
|View full text |Cite
|
Sign up to set email alerts
|

Ionic permeability changes as the basis of the thermal dependence of the resting potential in barnacle muscle fibres

Abstract: SUNMMARY1. The thermal dependence of the resting potential of isolated barnacle muscle fibres was larger (1-2 mV/0 C) than predicted by Nernst's equation (about 0*2 mV/0 C). A comparative study was made of the influence on thermal dependence of parameters related to (a) passive permeability and to (b) Na extrusion. 6. Although a small effect by a Na electrogenic pump cannot be excluded, the largest part of the thermal effect on the resting potential is concluded to depend on temperature-induced variations in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The Q10's found for the shifts along the frequency axis (2 to 3) are of the same order as generally measured for (bio)chemical processes of vertebrates (e.g. Fischbarg, 1972). Temperature effects on retinal signals of mammals, as far as available, are in general agreement with the goldfish data (Liitzow, 1970;Penn & Hagins, 1972).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The Q10's found for the shifts along the frequency axis (2 to 3) are of the same order as generally measured for (bio)chemical processes of vertebrates (e.g. Fischbarg, 1972). Temperature effects on retinal signals of mammals, as far as available, are in general agreement with the goldfish data (Liitzow, 1970;Penn & Hagins, 1972).…”
Section: Discussionsupporting
confidence: 84%
“…The Q10's found for the shifts along the frequency axis (2 to 3) are of the same order as generally measured for (bio)chemical processes of vertebrates (e.g. Fischbarg, 1972 (Liitzow, 1970;Penn & Hagins, 1972). That the cut-off frequencies of the amplitude characteristics of e.r.g.…”
Section: Discussionsupporting
confidence: 59%
“…f u,cell is typically measured by using cell homogenates at high cell density (e.g., 50 million cells/ml; see Discussion below on the limitations of using a low cell density), and the value is usually much lower than that for f u,inc but is similar to that for f u,liver . f u,cell can also be measured with whole cells at 4°C with the correction of the pH-gradient effect (i.e., f u,cell = 1/partition coefficient at 4°C), where active processes by transporters and enzymes and membrane potentials are essentially shut down at low temperature (Dipolo and Latorre, 1972;Fischbarg, 1972). The f u,inc , on the contrary, is usually determined using cell homogenates or dead cells at lower cell densities, the same as under the incubation conditions for metabolic stability studies (e.g., 0.5-2 million cells/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, acclimation could produce certain fundamental changes in membrane composition, which may differentially influence the operation of channels for potassium, sodium, and chloride ions, as well as those concerned with leakage. Such a differential effect on the relative permeabilities of a membrane to different ions has been demonstrated in barnacles (Dipolo and Latorre, 1972;Fischbarg, 1972). Recently, it has been shown that the membrane potential can hyperpolarize beyond the potassium potential at high temperatures (White, 1983).…”
Section: Resting Potentialmentioning
confidence: 92%